Classroom Management Through Problem Solving: Teachers' Strategies in Realizing Quality Learning - M. Nur Mustafa; Hermandra Hermandra; Zulhafizh Zulhafizh (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This study aims to describe the classroom management through problem-solving strategies in realizing quality learning. This research was conducted by quantitative approach. The main data of this study was 108 high school teachers. The technique used for data collection is questionnaire. The analysis technique used descriptive statistics, factor analysis, normality test, and inferential statistical test through t and anova tests. The results of the analysis show that classroom management efforts through problem solving are categorized as good by all aspects. Every aspect is valid with Alfa Cronbach's 0.766, thus, normal. The analysis of categorical factors is relevant in analyzing the classroom management through problem solving in realizing quality learning, which is above 0.7. In correlational analysis and one t-test of sample, all data are correlated and have significant role seen by the value of sig. 0.000 < 0.05. The Anova test through the linear path shows all the linearity as it impacting the problem solving in classroom management with value of F 0.000 < 0.05. Each aspect has its own characteristics on its implementation in learning. It shows that classroom management through problem solving can be a strategy in realizing quality learning.